Outdoor Solar Powered Smart Cloth Hanger: Retracting Clothes Upon Sensing Rain - Hassim, Hairul Mubarak (Multidisciplinary Applied Research and Innovation, 2023)
The uncertain weather problem has been causing people to have a hard time doing their laundry as daily chores due to the primary issue that will be encountered when the sunny weather changes to rainy, drying garments is one of the unpleasant household tasks. With the right innovation, it can make living easier for people as The Smart Hanger is able to pull the cloth into a safe area in 30 seconds after the rain is detected¸moved in rotational movement for the cloth to enter the shelter. The selected material chosen is corrosion resistant and very durable corresponding to the function of the machine and how it is exposed torain and sunlight in the outdoors. The Smart Hanger that has the ability to set the cloth movement and these mechanism work when Smart Solar-powered clothes hangers detect rain and automatically activate the mechanism while also being powered fully by solar power while the DC motor will rotate the belt which transfers the signal to the bevel gear and finally to the wire guide roller to move the string right away. Basically, this idea is effective in line with its goal of reducing the load of carrying out our daily tasks and for future development should include adding a roller or wheel to this smart hanger to make it easier to move as needed and more suitable if the user wants to transfer it to a more convenient location.